2016
DOI: 10.1186/s12915-016-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of BMP and Hes1/Hairy1 signaling in the dorsal neural tube underlies the transition from neural crest to definitive roof plate

Abstract: BackgroundThe dorsal midline region of the neural tube that results from closure of the neural folds is generally termed the roof plate (RP). However, this domain is highly dynamic and complex, and is first transiently inhabited by prospective neural crest (NC) cells that sequentially emigrate from the neuroepithelium. It only later becomes the definitive RP, the dorsal midline cells of the spinal cord. We previously showed that at the trunk level of the axis, prospective RP progenitors originate ventral to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 66 publications
11
65
0
Order By: Relevance
“…The newly formed roof plate, in turn, becomes an important source of BMPs as well as Wnts, which organize DV pattern and are essential for dorsal interneuron specification (reviewed in (Chizhikov and Millen 2004). Earlier in development, the roof plate lineage shares a common progenitor with the neural crest lineage (Krispin et al 2010, Nitzan et al 2016). The Zic family of zinc-finger transcription factors is essential for the formation of both lineages during early neural development (Aruga et al 1996, Nakata et al 2000, Elms et al 2003, Elsen et al 2008, Milet et al 2013, Teslaa et al 2013, Plouhinec et al 2014, Sedykh et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The newly formed roof plate, in turn, becomes an important source of BMPs as well as Wnts, which organize DV pattern and are essential for dorsal interneuron specification (reviewed in (Chizhikov and Millen 2004). Earlier in development, the roof plate lineage shares a common progenitor with the neural crest lineage (Krispin et al 2010, Nitzan et al 2016). The Zic family of zinc-finger transcription factors is essential for the formation of both lineages during early neural development (Aruga et al 1996, Nakata et al 2000, Elms et al 2003, Elsen et al 2008, Milet et al 2013, Teslaa et al 2013, Plouhinec et al 2014, Sedykh et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…References: Gnathostomes; Mouse, BMP2 , BMP6 , BMP7 , and Gdf7 are expressed in roof plate, BMP4 in the whole spinal cord E9.5 then restricted to dorsal ectoderm by E10.5 . Chick, BMP4 , BMP7 , and Gdf7 are in the roof plate, BMP6 expressed through out spinal cord except roof plate . Lizard, BMP4 in the roof plate .…”
Section: Patterning the Vertebrate Spinal Cord: The Ap Axismentioning
confidence: 99%
“…Following the completion of NC EMT, the dorsal neuroepithelium regains epithelial characteristics and generates the RP (Nitzan et al, ). The RP is a bona fide CNS cell type that constitutes the definitive dorsal midline of the spinal cord and behaves as a signaling center necessary for interneuron development (Chizhikov & Millen, ).…”
Section: The End Of Nc Emt and Transition Into Rpmentioning
confidence: 99%
“…The early responsiveness of RP progenitors to BMP suggested that this factor may, nevertheless, be important for initial specification of these cells. In fact, exposure of dorsal tube cells at the NC stage to high levels of BMP signaling induced premature RP traits, such as the RP marker Hairy1 , while concomitantly inhibiting NC production (Nitzan et al, ). This is consistent with RP precursors being extensively exposed to BMP when compared to NC which “sense” the factor and undergo rapid EMT.…”
Section: The End Of Nc Emt and Transition Into Rpmentioning
confidence: 99%
See 1 more Smart Citation